The Suitability of Moringa oleifera Leaf Meal Supplementation to Commercial Diets on the Growth and Survival of Oreochromis niloticus Fry - Romeo Caturao; Michel Atilano; Rexie Urbina (Philippine Association of Institutions for Research, Inc., 2017)
Proper fish nutrition and adequate feeding are necessary for high fish production. The study was conducted to determine the suitability of M. oleifera leaf meal supplementation to commercial diets on the growth performance of Oreochromis niloticus fry until fingerling size. Seven experimental diets were used with three replicates each arranged in a complete randomized design. Treatments 1, 3 and 5 were given commercial diets only, treatments 2, 4, and 6 with 10% M. oleifera leaves and 90% commercial diets. Treatment 7 was the control with rice bran. Each treatment was stocked with 50 fry with an average weight of 1.76+0.112 and an average length of 47.65+1.78 and feed for two months. Data gathered were analyzed using the One-Way ANOVA to determine significant difference among treatments. Duncan's Multiple Range Test (DMRT) was used to determine the significant difference between treatment means. All test used 0.05 level of significance. Results showed significant differences among treatments. Treatment 4 had the highest average weight of 6.83+0.145 g, an average length of 65.97+0.251 mm, and survival rate of 86.0+2.646% after eight weeks of culture. Growth and survival of Oreochromis niloticus could be enhanced by adding 10% dried M. oleifera leaf meal supplementation to commercial diet.